KESOPANAN TINDAK TUTUR MENYURUH DALAM BAHASA INDONESIA - Ngusman Manaf (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to describe verbal expressions by Indonesian speakers in the speech act of commanding politely in Indonesian. The data sources were Indonesian speech acts made by native speakers of Indonesian; they were collected through observations and interviews. The data were qualitatively analyzed using pragmatic theories. The results of the analysis show that there are two primary ways that native speakers of Indonesian use to perform the speech act of commanding politely. First, commands are performed by means of phatic expressions showing intimacy and appreciation. Second, they are performed through phatic expressions showing a minimization of force and burden. Keywords: speech acts, phatic express